Promosi Kesehatan dengan Media Poster terhadap Perubahan Pengetahuan PHBS pada Rumah Tangga - Septaria Nurhidayati (Jurnal Pengabdian Masyarakat Saga Komunitas, 2023)
Background: According to the World Health Organization (WHO) in 2018, as many as 2.4 billion people in the world or 1 out of 3 people do not have access to adequate sanitation facilities, and less than 1 billion people defecate in the open, causing various negative impacts, especially related to the spread of disease and public health. In Indonesia in 2018, the National Health Survey showed that the achievement of houses implementing PHBS (classification IV) was only around 39.22%. in Bekasi Regency implementing household PHBS at the Cibatu Health Center, In 2022, the percentage of households with PHBS is 45.3%. and in 2023 the percentage of households with PHBS is 64.5%. This happens due to the community's lack of knowledge and attitudes toward implementing PHBS culture in everyday life. Objectives: The purpose of this community service is to provide education in the form of health promotion regarding the culture of implementing PHBS in household settings in daily life at the Posyandu Tunas Mekar XIII in the working area of the Cibatu Health Center, Bekasi Regency. Methods: The method used is health promotion regarding the culture of implementing PHBS in household arrangements related to preventing the occurrence of disease by implementing PHBS in Kp. Pegaulan in the Work Area of the Cibatu Health Center, Bekasi Regency. This activity was carried out at the Tunas Mekar XIII Posyandu Kp. Social intercourse in Bekasi Regency. The target of this activity is all housewives who live in the Tumas Mekar XIII Posyandu area, Kp. Pegaulan, Bekasi Regency. Educational media used are posters and leaflets. The pre-test and post-test are used to measure this activity's success. Results: The results obtained from the implementation of health promotion activities to increase public knowledge in cultivating the correct implementation of household PHBS in everyday life are 75% or as many as 18 people. Conclusion: The conclusion drawn from the results of this activity is that there are still people who do not know and have not implemented PHBS properly and correctly, this is one of the echoes of the causes of a disease.